Effect of luseogliflozin on liver fibrosis differs depending on alcohol consumption in patients with type 2 diabetes - Hiroyuki Ito; Ryota Someya; Tomoko Koyanagi; Chiaki I; Shun Miura; Suzuko Matsumoto; Hideyuki Inoue; Shinichi Antoku; Tomoko Yamasaki; Toshiko Mori; Michiko Togane (Journal of Diabetes Investigation)
ABSTRACT Aim Changes in FIB‐4 levels after the initiation of luseogliflozin therapy were compared between patients with type 2 diabetes according to the presence or absence of alcohol consumption. Methods A total of 192 patients with type 2 diabetes who continued luseogliflozin therapy for over 12 months were retrospectively investigated. The primary outcome was the change in FIB‐4. The secondary outcomes were changes in HbA1c, body weight, and serum albumin concentration. A current drinker was defined as an individual consuming >20 g ethanol equivalent/day. Patients were classified according to their risk of developing liver fibrosis into the low‐risk (FIB‐4 < 1.3) and intermediate/high‐risk (FIB‐4 ≥ 1.3) groups. Results In the low‐risk group, while FIB‐4 increased dramatically from 0.91 ± 0.30 at the baseline to 1.14 ± 0.34 at 12 months in drinkers (n = 27), non‐drinkers (n = 79) showed no significant change (0.87 ± 0.22–0.91 ± 0.26). In the intermediate/high‐risk group (n = 63), although the FIB‐4 in drinkers (n = 23) showed no significant change (2.18 ± 1.00–2.16 ± 0.93), it significantly decreased from 2.10 ± 0.87 to 1.80 ± 0.68 in non‐drinkers (n = 63). In both the low‐ and intermediate/high‐risk groups, HbA1c and body weight significantly decreased in both drinkers and non‐drinkers. Serum albumin concentrations significantly increased in both drinkers and non‐drinkers in the low‐risk group. Although serum albumin concentration did not significantly change in drinkers, it dramatically increased in non‐drinkers in the intermediate/high‐risk group. Conclusions HbA1c levels and body weight decreased in patients with type 2 diabetes after initiating luseogliflozin therapy, regardless of drinking habits. However, it is desirable to limit alcohol consumption when considering its effects on liver fibrosis.